China's guided memory: How historical events are remembered, glorified, reinterpreted, and kept quit - Hanns Günther Hilpert; Frédéric Krumbein; Volker Stanzel (Stiftung Wissenschaft und Politik (SWP), 2020)
In 2019, China commemorated several anniversaries of politically significant events in its recent history: the May Fourth Movement (100 years), the foundation of the People's Republic of China (70 years), the Tibet Uprising (60 years), the beginning of the reform and opening policy (40 years), and the massacre on Tiananmen Square (30 years). How China officially commemorates these events - or does not - weighs heavily on the country's domestic and foreign policy. The state-constructed interpretations of history as a claim to power are directed not only at Chinese society, but also at foreign partners interacting with China, especially governments and companies. The concealment of problematic events from the past is alarming, not least because it increases the danger that historical mistakes will be repeated.
Keywords: 320